Microwave Absorption Performance of La0.7Sr0.3MnO3/AC Composite Material Based on Activated Carbon from Gnetum gnemon Seed Shell - Priambodo, Danang Pamungkas; Saptari, Sitti Ahmiatri; Tjahjono, Arif; Manawan, Maykel T; Taryana, Yana; Hadiyawarman; Admi, Ratna Isnanita (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2025)
The 5G internet network has been proven to facilitate daily life for people and render electronic devices such as smartphones as an integral component of people's daily routine. However, in conjunction with the ease of use, there is an issue of electromagnetic radiation. To cope with this issue, magnetic and dielectric composite microwave absorber materials have been undertaken. To address this, we investigated the limitations of activated carbon composite material from Gnetum gnemon seed shells (AC) on the microwave absorption ability of (La0.7Sr0.3MnO3)1-y/(AC)y. The composite material (La0.7Sr0.3MnO3)1-y/(AC)y (y = 0; 0.3; 0.5; 0.7) was synthesized through a stirring process with a 96% ethanol catalyst using La0.7Sr0.3MnO3 synthesized by sol-gel method and activated carbon material from Gnetum gnemon seed shell (AC) synthesized by chemical activation method. The XRD and SEM characterizations indicated a single-phase structure, with smaller crystals and particles that were uniformly distributed throughout the composite sample. The presence of activated carbon grains from Gnetum gnemon seed shells (AC) were observed between the La0.7Sr0.3MnO3 grains in the composite sample. The EDS results confirmed the material’s purity. VNA characterization demonstrated that (La0.7Sr0.3MnO3)1-y/(AC)y was capable of producing two reflection loss troughs with the largest absorption percentages recorded at 82.99% and 85.82% respectively within the frequency range of 8 – 12 GHz. This research highlights the significance of controlled composite composition in enhancing microwave absorption capability, particularly in perovskite-based composites with biomass-activated carbon, which holds a considerable promise for applications in electromagnetic wave attenuation and absorption technologies.